ANALISIS PELAKSANAAN PROGRAM BLT TERHADAP KEBUTUHAN RUMAH TANGGA MASYARAKAT NELAYAN DESA DENDUN - Topati, Galih; Juliyanto, Dimas; Maryanto, Sigit (Journal Education and Government Wiyata, 2025)
This research aims to analyze the use of Direct Cash Transfer (BLT) in Dendun Village, especially among the fishing community. The BLT policy was implemented by the Dendun Village Government as an effort to help fulfill the needs of fishing households. In its implementation, the government set criteria for beneficiaries that had to be met so that the assistance could be allocated with the right target. This research used a qualitative method with data collection techniques through direct observation and interviews with the village head, village officials, RT heads, and BLT beneficiaries. The results showed that the Dendun Village Government allocated funds of Rp15,000,000 (fifteen million rupiah) that were disbursed monthly. This policy had a positive impact on the management of BLT funds, especially in fulfilling the basic needs of the fishing community. The successful implementation of the BLT program was influenced by effective communication between the village government and the community, optimal resources, disposition or positive attitudes from policy implementation and the village bureaucratic structure in Dendun Village which played a significant role in the successful implementation of the BLT program. The implications of this research emphasize the importance of an attitude of responsibility, openness, as well as commitment and honesty from the village head and the implementation team. Thus, the BLT program in Dendun Village ran well and provided real benefits for the fishing community, which tends to be vulnerable to income fluctuations.